Implementation of Digital Transformation in HIPSI SMEs: A Qualitative Analysis of Strengthening Local Community Digital Capabilities - Muhammad Fahmul Iltiham; Muhammad Nizar (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Purpose: The increasing importance of digital innovation as a driver of business transformation across various industries remains underexplored in the context of SMEs. This study aims to address this gap by examining the direct effects of digital orientation and digital capability on digital innovation and assessing the mediating role of digital innovation in the relationship between organizational performance and these driving factors. Design/methodology/approach: This qualitative study analyzes data collected from 20 HIPSI SMEs in Pasuruan, Indonesia. Data were obtained through interviews and document reviews and analyzed using thematic analysis and structural modeling techniques with SmartPLS. Findings: The findings reveal that digital orientation and digital capability significantly influence digital innovation. Furthermore, digital innovation mediates the effect of digital orientation and digital capability on financial and non-financial performance. This demonstrates the critical role of digital innovation in enhancing organizational performance by leveraging digital resources effectively. Practical implications: This study highlights the need for SMEs to adopt a digital-oriented mindset and invest in developing digital capabilities to harness the potential of emerging digital technologies. This strategic alignment can foster innovation, improve competitiveness, and strengthen community digital empowerment. Originality/value: This research provides a novel framework that links digital orientation, digital capability, and innovation to organizational performance within the SME sector. It fills a critical gap in the literature by emphasizing the mediating role of digital innovation and offering insights into the digital transformation of local business communities.